CGX1037 is a novel PKC isoform delta selective inhibitor in platelets. (February 2015) - Bhavanasi, Dheeraj; Kostyak, John C.; Swindle, John; Kilpatrick, Laurie E.; Kunapuli, Satya P.
Abstract Platelets upon activation change their shape, aggregate and secrete alpha and dense granule contents among which ADP acts as a feedback activator. Different Protein Kinase C (PKC) isoforms have specific non-redundant roles in mediating platelet responses including secretion and thrombus formation. Murine platelets lacking specific PKC isoforms have been used to evaluate the isoform specific functions. Novel PKC isoform δ has been shown to play an important role in some pathological processes. Lack of specific inhibitors for PKCδ has restricted analysis of its role in various cells. The current study was carried out to evaluate a novel small molecule PKCδ inhibitor, CGX1037 in platelets. Platelet aggregation, dense granule secretion and western blotting experiments were performed to evaluate CGX1037. In human platelets, CGX1037 inhibited PAR4-mediated phosphorylation on PKD2, a PKCδ-specific substrate. Pre-treatment of human or murine platelets with CGX1037 inhibited PAR4-mediated dense granule secretion whereas it potentiated GPVI-mediated dense granule secretion similar to the responses observed in murine platelets lacking PKCδ· Furthermore, pre-treatment of platelets from PKCδ−/− mice with CGX1037 had no significant additive effect on platelet responses suggesting the specificity of CGX1037. Hence, we show that CGX1037 is a selective small molecule inhibitor of PKCδ in platelets.